Enhancing Students’ Reading Proficiency through Game-Based Learning - Cindy Pearl M. Quita; Ma. Vivienne S Salon; Teresita H. Borres; Estrella Y. Dacillo (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
Game-Based Learning (GBL) is a teaching approach incorporating enjoyable and interactive activities into the learning process to engage students and enhance their reading proficiency. The study adopted the eight steps of R&D model design by Gall and Borg in 1989. It aimed to develop, validate, and test the effectiveness of the instructional materials on enhancing the reading proficiency level of Grade 7 students of Dologon National High School- Kiharong Annex for school year 2024-2025. Specifically, it sought to: develop instructional materials on enhancing the reading proficiency level of students using game-based learning; validate the materials by subjecting them for evaluation by the teacher-experts and pilot learners; revise the material based on the suggestions and recommendations of the teacher-experts and pilot learners; and test the effectiveness of the developed, validated, and revised instructional materials in enhancing reading proficiency. The study employed a quasi-experimental design which used two intact sections as experimental and control groups. The research utilized the adapted questionnaires in assessing the teacher-experts and students’ evaluation on the GBL-IMs. Descriptive statistics and ANCOVA were used in the study. The findings of the study revealed that teacher-experts evaluation on GBL was “Highly Eligible”, and students’ evaluation was “Strongly Agree” which mean that “The criteria were completely met”. Moreover, GBL group has a higher reading proficiency increase compared to the non-GBL group and there was a significant difference between their pretest and posttest scores after the intervention.